Inased (inhaled sedation in ICU) trial protocol: a multicentre randomised open-label trial. Issue 2 (19th February 2021) - Bailly, Pierre; Egreteau, Pierre-Yves; Ehrmann, Stephan; Thille, Arnaud W; Guitton, Christophe; Grillet, Guillaume; Reizine, Florian; Huet, Olivier; Jaber, S; Nowak, Emmanuel; L'her, Erwan
Abstract : Introduction: The use of sedation in intensive care units (ICUs) is necessary and ubiquitous. The impact of sedation strategy on outcome, particularly when delivered early after initiation of mechanical ventilation, is unknown. Evidence is increasing that volatile anaesthetic agents could be associated with better outcome. Their use in delirium prevention is unknown. Methods and analysis: This study is an investigator-initiated, prospective, multicentre, two-arm, randomised, control, open-trial comparing inhaled sedation strategy versus intravenous sedation strategy in mechanically ventilated patients in ICU. Two hundred and fifty patients will be randomly assigned to the intravenous sedation group or inhaled sedation group, with a 1:1 ratio in two groups according to the sedation strategy. The primary outcome is the occurrence of delirium assessed using two times a day confusion assessment method for the ICU (CAM-ICU). Secondary outcomes include cognitive and functional outcomes at 3 and 12 months. Ethics and dissemination: The study has been approved by the Regional Ethics Committee (CPP Ouest) and national authorities (ANSM). The results will be submitted for publication in peer-reviewed journals. Trial registration number: NCT04341350